Inhomogeneous coupling induced quantized distribution of photonic states in Kagome lattices across different Landau levels - Liyun Tao; Yahong Liu; Xin Zhou; Lianlian Du; Shaojie Ma; Xiaoyong Yang; Jintao Zhang; Zhenfei Li; Kun Song; Xiaopeng Zhao (Communications Physics)
Abstract Recent progress has demonstrated that synthetic gauge fields can mimic Landau quantization in materials including graphene and lattices for sound and light. However, despite using graphene-like structures with strain-induced textures in prior photonics, it is hard to capture the experimental attainment of distinct photon bound states for various Landau levels. In this work, we introduce an experimental framework for achieving photonic Landau quantization. We present the quantized distribution of photonic states across different Landau levels in a two-dimensional Kagome metal lattice. By introducing inhomogeneous coupling, we implement two kinds of pseudomagnetic field, which quantize spectrums and quantizes distribution of photonic states, respectively. We experimentally observe that the electric field distribution is localized according to the positional attributes of different Landau levels. Our proposed system is more straightforward to implement, and it opens an avenue to explore photonic states at non-zero Landau levels, which are predicted to demonstrate some interesting physical phenomena.